2004
DOI: 10.1111/j.1432-1033.2004.04229.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor XII binding to endothelial cells depends on caveolae

Abstract: It is now generally accepted that factor XII (FXII) binds to cellular surfaces in the vascular system. One of the suggested receptors of this binding is the glycosylphosphatidylinositol-anchored urokinase-like plasminogen activator (u-PAR) harbored in caveolae/lipid rafts. However, binding of FXII to human umbilical vein endothelial cells (HUVEC) has never been shown to be localized to these specialized membrane structures. Using microscopical techniques, we here report that FXII binds to specific patches of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…In our previous work we demonstrated that in CHO-K1 pretreated with methyl-β-cyclodextrin H-kininogen endocytosis is prevented and it did not colocalize with transferrin in the early phase of the endocytic process strongly indicating that the endocytosis is not dependent on clathrin [ 17 ]. Consistent with our findings, FXII binding to HUVECs depends on intact caveolae on the cellular surface [ 31 ], and caveolae harbor proteoglycans [ 32 ]. The bradykinin-free H-kininogen does not internalize as shown in the present work ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In our previous work we demonstrated that in CHO-K1 pretreated with methyl-β-cyclodextrin H-kininogen endocytosis is prevented and it did not colocalize with transferrin in the early phase of the endocytic process strongly indicating that the endocytosis is not dependent on clathrin [ 17 ]. Consistent with our findings, FXII binding to HUVECs depends on intact caveolae on the cellular surface [ 31 ], and caveolae harbor proteoglycans [ 32 ]. The bradykinin-free H-kininogen does not internalize as shown in the present work ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that FXII can bind to ECs in a zinc-dependent manner via urokinase-like plasminogen activator receptor (u-PAR), cytokeratin 1 and the complement receptor gC1qR1 (14,31,32). ECs are also able to produce an extracellular matrix protein which can serve as a zinc-independent binding site for FXII (13).…”
Section: Discussionmentioning
confidence: 99%
“…HK and/or HKa binds to CK-1 through D3 and/or D5, while uPAR and gC1qR bind primarily to D5 (Mahdi et al, 2004). Interestingly, gC1qR is also a binding site for factor XII (Joseph et al, 1996) whereby binding depends on caveolae on endothelial cells and caveolae harbor GPI-anchored PGs (glypicans) (Schousboe et al, 2004). Interestingly, gC1qR is also a binding site for factor XII (Joseph et al, 1996) whereby binding depends on caveolae on endothelial cells and caveolae harbor GPI-anchored PGs (glypicans) (Schousboe et al, 2004).…”
Section: Introductionmentioning
confidence: 99%